ANALISIS SRTATEGI KOMPETITIF PT PERUSAHAAN GAS NEGARA (PERSERO) TBK DALAM KEGIATAN USAHA HILIR MIGAS DI INDONESIA - , Dian Restiyani, Dr. Tarsisius Hani Handoko, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Changing business environment requires companies to constantly adapt and respond quickly in order to survive or compete in an industry. This also applies to companies engaging in the downstream oil and gas business activities in Indonesia. When a number of companies began to appear along with the increasing domestic natural gas demands and supported by government policy in regards to the natural gas utilization, the competition in the downstream oil and gas business activities in Indonesia has become increasingly competitive. In order to be able to continue managing its growth and sustainability, the company requires possessing an effective competitive strategy in accordance with the changing dynamics of the business environment. This research aims to analyze the external and internal environmental factors and formulate the most suitable competitive strategies alternative for PT Perusahaan Gas Negara (Persero) Tbk (\"PGN\"). The external environment analysis is performed through macro environmental analysis based on political, economic, social and technology environment factors as well as industry analysis implementing five forces theory, strategic groups maps and competitive strengths in obtaining a key success factor in downstream oil and gas business activities competition in Indonesia. Internal analysis is conducted through resource analysis and value chain analysis using resources and capabilities elements as well as competitive strength analysis using VRIO in identifying a sustainable competitive advantage possessed by PGN. By applying the external environment and internal analyses to formulate business strategies in competing in downstream oil and gas PGN business activities in Indonesia, result on alternative competitive strategy which best suits PGN conditions obtained is through Best Cost Provider Strategy. Best Cost Provider Strategy aims to focus on delivering more value to consumers (superior value) by combining differentiation and cost leadership.